Description of a new species of Micrencaustes (subgenus Mimencaustes Heller) (Coleoptera: Erotylidae: Encaustini) from China - Li, Jing; Ren, Guo-Dong (Zootaxa, 2006)
The subgenus Mimencaustes Heller is recorded from mainland China for the first time. One new species, Micrencaustes (Mimencaustes) acridentata sp. nov., is described in this paper. Type specimens are deposited in the Institute of Zoology, Chinese Academy of Sciences, Beijing, China and the Museum of Hebei University, Baoding, China.